IMPACT OF MARKETING STRATEGIES ON YOUTH PURCHASING BEHAVIOR: A CASE STUDY OF MOBILE PHONE INDUSTRY - Ghafoor Awan, Abdul; Fatima, Arooj (British Journal of Marketing Studies, 2014)
Marketers consider youth as an important segment in recent globalized world. Due to their large number, accessibility to readily available information and massive internet usage they are difficult to ignore. This research paper aims to study the impact of marketing strategies on youth purchasing behavior in selection of mobile phone network. The study has focused that how these strategies used by mobile phone networking companies in Pakistan influence the purchase decision of youth in selection of their mobile phone network. Youth purchasing behavior has been taken as dependent variable to be influenced by various independent variables which are service quality, pricing, value offered, trust and switching cost. Primary data was collected by using self-administrative questionnaire with a sample size of 230 participants. Regression analysis was done for results analysis. The proposed research shows that youth preferred the mobile phone network with best service quality (quality in terms of all SMS, call and internet) at reasonable prices. Other factors like value offered by mobile phone networks, trust on the company and the switching cost also impact the purchasing decisions of youth in selection of mobile phone network.